"Craigslist is Nothing More than an Internet Brothel": Sex Work and Sex Trafficking in U.S. Newspaper Coverage of Craigslist Sex Forums. Issue 6 (24th July 2021) - Reynolds, Chelsea
ABSTRACT: In spring 2018 the U.S. federal government forced Craigslist's sex forums closed. A new anti-sex trafficking law, FOSTA-SESTA, made exceptions to the Communications Decency Act, holding websites accountable for online "prostitution." This study used critical discourse analysis to trace how U.S. newspaper articles reported on Craigslist sex forums ( N = 280) during 13 years of coverage preceding FOSTA-SESTA. Nearly 70% of the stories (n = 194) covered Craigslist sex forums through frames that emphasized sex work and sex crimes or regulatory efforts against Craigslist, focusing primarily on preventing digital sex trafficking. Newspaper narratives supported online surveillance efforts championed by conservative lawmakers across the country, who used Craigslist as a scapegoat for sex trafficking and online "prostitution." Consensual sex work was symbolically annihilated in coverage – evidence of a dominant representational paradigm that produced epistemic violence against sex workers. Media and policy implications are discussed.